Ceria-based redox materials for thermochemical looping fuel generation: A review - Sachan D.; Pimple S.Y.; Singh R. (My University, 2025)
The world needs alternative energy sources due to the aggravating problem of global warming with the use of fossil fuels. Thermochemical routes utilizing thermal energy, appears to be a promising method for splitting H2O/CO2 into green fuels such as H2/CO with the help of a redox mediator/oxygen carrier (OC). This review focuses on one of the most promising OC, ceria, as a redox material due to its exceptional thermal stability at elevated temperatures and rapid reaction kinetics. The influence of various parameters, such as reduction (TR), oxidation temperature (TO), and the difference (ΔT= TR-TO) during the ceria-based thermochemical cycling process was analyzed utilizing data in open literature from 2006 onward. The discussion encompasses the impact of these parameters on fuel yield, oxygen yield, and fuel to oxygen yield ratio. Introduction of a novel reactor train system (RTS) combined with oxygen pumping is found to enhance thermal-to-fuel efficiency to an impressive 40%, marking a significant advancement in the field. © 2025 Indian Institute of Technology (Banaras Hindu University).